The role of the judiciary in protecting the Levantine agriculture through documents Of sharia courts in the eighteenth And nineteenth centuries - كامل بشار; سمر بهلوان; رامي الضللي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Throughout its history, Damascus maintained its position as an important commercial center in the region, supported by a number of factors. Damascus and its surrounding fertile agricultural lands gave it a leadership position in agricultural production. The damascene farmer, who masterminded his work, is supported by abundant rains, snow, and surface rivers, the most important of which is the Barada River, famous for the fame of Damascus. This agricultural abundance supported many crafts and industries that have become traditional in this ancient city, and these works culminate in what the people of Damascus were known for in the field of trade, as they became famous and became a commercial center for Damascene products and the products of the surrounding and even distant countries. However, this reality has changed since the beginning of the eighteenth century, as Damascus has fallen under the influence of a mass of complications, the most important of which are the foreign concessions that were constantly increasing due to the weakness of the ottoman empire and its falling under the growing European influence. From time to time, every attempt at reform turned into a new opportunity for those classes to open a new struggle over ownership and the wealth it generates at the expense of the rest of society. The damascene peasant fell under the pressure of exorbitant taxes, royalties, encroachments of landlords and inevitable struggle over agricultural ownership and a struggle over water sources, and entered into a conflict. The labyrinth of debts and exorbitant with great danger, and he has no choice but to resort to the judiciary in an attempt to remove all these grievances from him.